2009
DOI: 10.1080/01635580903285072
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol and Piceatannol Inhibit iNOS Expression and NF-κ B Activation in Dextran Sulfate Sodium-Induced Mouse Colitis

Abstract: Inflammatory tissue injury has been implicated in tumor promotion and progression. 3,5,4'-trihydroxy-trans-stilbene (resveratrol) and 3,4,3', 5'-tetrahydroxy-trans-stilbene (piceatannol), 2 structurally related plant polyphenols, have been reported to possess antioxidant, anti-inflammatory, and chemopreventive properties. This study was aimed at investigating the possible protective effects of resveratrol and piceatannol against dextran sulfate sodium (DSS)-induced inflammation in mouse colonic mucosa. Adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 48 publications
7
79
0
Order By: Relevance
“…Indeed, activation of these pathways has been described in conjunction with dextran sulfate sodium-induced colitis in mice and TNBS-induced colitis in rodents (Bai et al, 2007;Kretzmann et al, 2008;Youn et al, 2009;Fitzpatrick et al, 2011b). Moreover, we have reported that Vido inhibits activation of these intracellular signaling pathways in the mouse colon and murine splenocytes (Fitzpatrick et al, 2011b).…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, activation of these pathways has been described in conjunction with dextran sulfate sodium-induced colitis in mice and TNBS-induced colitis in rodents (Bai et al, 2007;Kretzmann et al, 2008;Youn et al, 2009;Fitzpatrick et al, 2011b). Moreover, we have reported that Vido inhibits activation of these intracellular signaling pathways in the mouse colon and murine splenocytes (Fitzpatrick et al, 2011b).…”
Section: Discussionmentioning
confidence: 78%
“…In a majority of studies, weight loss was less in animals given Resveratrol [13,15,16,20,21,23,24,28,33,39]. While few studies showed no difference between groups [37,38].…”
Section: Reduced Clinical Symptomsmentioning
confidence: 99%
“…Inducible nitric oxide synthase (iNOS), which initiates NO production, is up regulated in a state of chronic intestinal inflammation [27]. Resveratrol generally diminishes iNOS protein expression [13,16,28] and NO production [29,30]. One study dissimilarly found resveratrol to raise NO levels above baseline values [21].…”
Section: Reduced Proinflammatory Mediatorsmentioning
confidence: 99%
See 2 more Smart Citations